PENERAPAN MEDIA CROSSWORD LABS BERBASIS MODEL CTL TERHADAP HASIL BELAJAR MEMAKNAI KOSAKATA BERAWALAN ME- SISWA KELAS IV - Winarni, Winarni; Yuwono, Agus; Dewi Purwati, Panca; Widiarti, Nuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low learning outcomes of students in the material on understanding vocabulary starting with me- for grade IV students of SD Negeri Paketiban 01. This was caused by the lack of interactive media that actively involved students and a learning model that was less contextual. Therefore, this study aims to examine the effectiveness of the application of interactive Crossword Labs media based on the Contextual Teaching and Learning (CTL) learning model in improving learning outcomes in the material of interpreting vocabulary starting with me- for fourth grade students of SD Negeri Paketiban 01. This study uses mixed methods, namely a research method that begins with the collection of quantitative data through learning outcome tests, then continues with the collection of qualitative data obtained through the results of observations of learning activities in the application of Crossword Labs media based on the CTL model for fourth grade students of SD Negeri Paketiban 01. The subjects of the study were 16 fourth grade students of SD Negeri Paketiban 01. The results of the quantitative data analysis showed that the application of Crossword Labs media based on the CTL model was effective in improving learning outcomes, with evidence of an increase in the average value of student learning outcomes by 20.5 points, from 61.25 (pretest) to 81.75 (posttest). This increase was also followed by an increase in classical completeness of 43.75%, from 43.75% to 87.50%. In addition, the N-gain analysis conducted strengthened the increase in student learning outcomes in the material of interpreting vocabulary beginning with me- by 0.54 which is included in the moderate criteria. Meanwhile, the results of qualitative data analysis showed that in general students strongly agreed that the Crossword Labs media based on the CTL model had a positive impact on motivation, understanding, and learning outcomes in the material of interpreting vocabulary beginning with me-. Thus, it can be concluded that the Crossword Labs media based on the CTL model is effective in improving the learning outcomes of the material of interpreting vocabulary beginning with me- of grade IV students of SD Negeri Paketiban 01.